Diagnosis as a Dynamic Process in Traditional Chinese Medicine: From Pattern Differentiation to Longitudinal Therapeutic Adaptation - Carlos Aurélio Silva Pereira (Revista de Ciências Médicas & Saúde (RCMS), 2026)
Background Pattern differentiation (Bian Zheng) is a central component of diagnosis and therapeutic decision-making in Traditional Chinese Medicine (TCM). Although commonly described as the basis for individualized treatment, patterns are frequently investigated as relatively static diagnostic categories. This approach may insufficiently represent a clinical system in which symptoms, tongue and pulse findings, functional relationships, therapeutic priorities, and consequently treatment strategies may change during the course of care. Objective To develop a conceptual framework for understanding TCM diagnosis as a dynamic and longitudinal process and to examine its possible relationships with contemporary concepts of physiological regulation, complex adaptive systems, network physiology, personalized medicine, and adaptive clinical research. Methods A structured narrative review was undertaken focusing on six interconnected domains: TCM pattern differentiation; diagnostic reliability and pattern research; temporal transformation of clinical states; homeostasis and allostasis; complex systems and network physiology; and research methodologies for individualized and adaptive interventions. The conceptual synthesis was organized according to nine propositions describing the relationship between clinical state, pattern identification, therapeutic intervention, reassessment, and subsequent therapeutic adaptation. Methodological quality principles for narrative reviews were informed by the SANRA framework. Results and conceptual synthesis Nine propositions are advanced: (1) a TCM pattern represents a clinical state rather than a permanent diagnostic identity; (2) treatment may modify the object being diagnosed; (3) clinical assessment should therefore be longitudinal; (4) pattern transformation may itself constitute clinically meaningful information; (5) the organism may usefully be approached as a complex adaptive system; (6) homeostasis and allostasis provide conceptual bridges for understanding stability through adaptation; (7) network physiology offers a contemporary framework for investigating multilevel physiological relationships; (8) individualized treatment requires research methodologies capable of accommodating justified therapeutic adaptation; and (9) longitudinal coherence may represent an additional dimension of diagnostic quality. Conclusion TCM diagnosis can be conceptualized as a sequence of state-dependent clinical interpretations rather than as a fixed diagnostic label. Under this framework, diagnostic change is not inherently evidence of inconsistency; when supported by corresponding clinical changes, it may represent appropriate tracking of an evolving biological system. We propose longitudinal diagnostic coherence as a testable construct describing the degree to which successive pattern diagnoses and therapeutic adaptations correspond coherently to observed changes in the patient's clinical state. This framework provides a basis for future prospective research using repeated measurements, multivariate physiological data, time-series approaches, pragmatic designs, and individualized trials.